2017
DOI: 10.12913/22998624/74135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Main Parameters Effects of Near-Field Earthquakes on the Behavior of Concrete Structures with Moment Frame System

Abstract: Amplitude and frequency content are two important features of earthquakes that are different for near and far-fault earthquakes and in most of the standards, the effects of near-field earthquakes in loading are not considered. Therefore, study and comparison of these effects on structures is necessary. In this paper, structural operation against near and far fault earthquakes for two near sites and two far sites is investigated. For this purpose and in order to achieve an operation point of a structural model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…This study focuses on the evaluation of the nonlinear seismic behavior of flat-bottomed reinforced concrete cylindrical silos under near-fault ground motions (NFGM) and far-field ground motions (FFGM). Though there is no fixed distance for the designation of the near-fault earthquakes; a distance range of (15-50) km is widely adopted by researchers and international codes as a reasonable value [18]. Zhou et al [19] studied the impact of NFGM characteristics on the structural demand of structures through attention relationships for 34 near-fault records.…”
Section: Nomenclature Cmentioning
confidence: 99%
“…This study focuses on the evaluation of the nonlinear seismic behavior of flat-bottomed reinforced concrete cylindrical silos under near-fault ground motions (NFGM) and far-field ground motions (FFGM). Though there is no fixed distance for the designation of the near-fault earthquakes; a distance range of (15-50) km is widely adopted by researchers and international codes as a reasonable value [18]. Zhou et al [19] studied the impact of NFGM characteristics on the structural demand of structures through attention relationships for 34 near-fault records.…”
Section: Nomenclature Cmentioning
confidence: 99%
“…As these earthquakes take place in the vicinity of an active fault, they have long-period pulse maps [2]. A thorough investigation of the main parameters of near-field earthquakes for concrete structures has been carried out by Talebi Jouneghani et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive studies have been carried out to address the main concerns on seismic isolation within the last decades [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. These studies show an accurately designed seismic isolation system effectively diminishes floor accelerations and inter-story drift ratios to acceptable levels without triggering unsatisfactorily large base displacements in case of far-field earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…The study also emphasized that the ordinary response spectrum factor method is outdated. Kourosh Talebi Jouneghani et al [6] reviewed behaviour of a 2D model of a six-storey frame building under pulse-like motions. They indicated that the displacement due to NF excitation exceeded design requirements by 30 %.…”
Section: Introductionmentioning
confidence: 99%